Successful Full Lactation Achieved by Mothers of Preterm Infants Using Exclusive Pumping - Ru, Xifang; Huang, Xiaofang; Feng, Qi (Frontiers in Pediatrics, 2020)
Background: Some mothers of preterm infants suffer from difficulties in initiating and maintaining adequate milk production. This study was designed to investigate the milk production in mothers of preterm infants using hospital-grade breast pumps and to study the nutrient content of their milk. Methods: This was an observational prospective study. Mothers of preterm infants with gestational age < 32 weeks or birth weight < 1500 g who were admitted to our hospital from August 2016 to December 2017 were recruited. A pumping diary and a questionnaire were completed by mothers (n = 30). Milk samples from before, during, and after each pumping session on days 7 and 14 postpartum were analyzed. Results: The median time to onset of lactogenesis II was 75.4 h. Mean milk output increased gradually, meeting key thresholds of 350g/d on day 6, 500 g/d on day 8, and close to 750 g/d on day 14. Then, all mean milk outputs were over 750 g/d. The mean milk output exceeded the mean feeding volume on days 7, 14, 21, 28, 35 and 42. Mothers using hospital-grade breast pumps had more cumulative milk production compared with mothers using hand expression. The milk yield on days 7 and 14 were positively correlated to that on days 21, 28, 35 and 42. Milk outputs on days 7, 14, and 42 of mothers with a pumping frequency of ≥ 6 times/d were greater than mothers with a pumping frequency of < 6 times/d. Threshold values for milk output on day 7 (cut-off, 406.8 g/d; sensitivity, 68.2%; specificity, 100%) and day 14 (cut-off, 518.0 g/d; sensitivity, 81.8%; specificity, 100%) were identified as predicting a milk output of more than 750 g/d on day 42. Fat and energy levels were higher in hind-milk than fore- or mixed-milk on days 7 and 14. Those who pumped ≥ 6 times/d had higher levels of fat, carbohydrate, and energy in their milk on day 7. Conclusion: Most preterm infants' mothers using a hospital-grade pump with a pumping frequency of ≥ 6 times/d can reach full lactation successfully. Nutrient analysis of the human milk should be performed.